Low-Concentration Hypochlorous Acid Drinking Water Alleviates Broiler Gut Microbial Load While Preserving Overall Growth Performance - Zonggang Li; Chang Liu; Dongyan Shao; Chune Tan; Yingqi Cao; Senzhong Deng; Teng Teeh Lim; Fei Xu (Toxics)
Hypochlorous acid has been attempted as an additive to animal drinking water in practical animal farming processes for water microbial quality control. Despite its potential, there is still a knowledge gap concerning the effects of hypochlorous acid on both poultry growth performance and gut microbial load. To address this gap, an animal study was conducted using flow cytometry to quantify the age-related microbial load in broiler manure and gut contents. We observed that the effect on growth performance was sustained only during the starter phase, with no significant impact throughout the entire production cycle. The treatment could reduce the microbial load of both fresh broiler manure and cecal contents. Despite this convergence in the duodenum, significant differences in microbial loads between the control and treatment groups persisted in the manure and cecal contents throughout the later stages. Our findings demonstrate that consuming low-concentration hypochlorous acid water over the long term can lower the microbial load in the broiler gut throughout the entire growth cycle without impacting overall growth performance. Future research on drinking or feed additives should incorporate microbial absolute quantification methods to achieve a more precise assessment of microbiota.